Optimizing Capital Structure in Southeast Asian Real Estate: The Role of Tangible Assets and Sales Growth (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study investigates the role of profit-based tangible assets and sales growth (ProTAPP) in enhancing the relationship between market ratios and financing decisions in property and real estate companies across Southeast Asia from 2019-2023. Using agency theory, pecking order theory, and trade-off theory, the research examines how EPS, TATO, and CR influence DER, with ProTAPP serving as a mediating variable. The analysis, based on panel data from ASEAN countries including Indonesia, Malaysia, Thailand, and Singapore, aims to provide practical insights for investors, corporate managers, and policymakers in optimizing financing strategies within the property and real estate sector. The study emphasizes the significance of tangible assets and sales growth dynamics in financial decision-making for achieving an optimal capital structure. Findings reveal that ProTAPP significantly mediates the relationship between EPS, TATO, CR, and DER in Southeast Asian property and real estate firms. The impact of these independent variables on DER through ProTAPP varies by country, reflecting specific market dynamics and company strategies. These results offer valuable guidance for developing more effective financing strategies in the sector.